Research and design university campus as an effective environment for the development of a student-innovator - Yulia A. Dianova; Svetlana V. Sergeeva (Saratov State University, 2023)
The relevance of the research is determined by the need to transform the educational environment of a modern university. Such environment is one of the conditions for the effective development of a student-innovator, who is motivated to carry out research and design, capable of searching for original ideas, innovative solutions, and project implementation. The purpose of the study is to reveal the essence of the concept of "research and design campus"; to determine the structure of students' readiness for innovation in the research and design campus; to identify the possibilities of the university research and design campus as an effective environment for the development of a student-innovator as illustrated by the example of Penza State Technological University (PenzSTU). The study shows that a research and design campus is an effective educational environment providing a system of opportunities for creativity, invention and personal self-development of a student-innovator at a modern university. The article reveals the essence of the concept of "research and design campus" from the standpoint of the environmental approach. The structure of the student's readiness for innovation activity in a research and design campus is presented. This structure consists of four functional blocks. The personal-motivational block includes the student's personal and professional qualities that determine his/her attitude to innovations of a career-oriented nature. The comprehension block contains ideas about the goals and content of the innovation activity. The implementation block includes qualities that ensure the creative implementation of an innovative project in practice. And the reflection block reflects the qualities associated with the student's assessment of his/her own innovation activity. Based on the practical case of Penza State Technical University, the authors identified and characterized organizational, substantive and technological capabilities of the campus for the development of a student-innovator. Organizational capabilities include the resource potential and the structuring of the environment. Substantive capabilities are presented by the software provision of the innovative activity of students in the university research and design campus. The technological capabilities of the environment include diagnostics, forecasting, designing, production of the result, that assumes a change in the environment and personality according to the goals. The article makes the conclusion about the potential of the research and design campus in the fields of organizing and implementing theoretical and applied research and projects, of providing students' collaborations and career guidance for student-innovators of a new formation